Effect of ultrasonic shot peening on strain controlled fatigue behaviour of low nickel austenitic stainless steel - Kumar C.S.; Mahobia G.S.; Chattopadhyay K. (My University, 2025)
In the present investigation effect of Ultrasonic shot peening (USP) treatment on strain controlled fatigue behavior of low nickel austenitic stainless steel (Low Ni ASS) was studied at room temperature. The gauge section of fatigue samples were USPed with 2 mm diameter hard steel shots for 3 min. Microstructural characterization of the USP treated samples were carried out using XRD, SEM and TEM techniques. Refinement of grains in the surface region was observed and grain size was found to be ≈17 nm from quantitative analysis of XRD patterns. Strain controlled fatigue tests were carried out at different total strain amplitudes (Δϵt/2) ranging from ±0.4% to ±0.8%. Fatigue life was increased significantly by 200% at lowest Δϵt/2 of ±0.4% whereas it was reduced at highest Δϵt/2 of ±0.8% by 50%. Fracture surfaces were characterized using SEM. © 2019 Elsevier Ltd.